Immunotherapy progress and clinical strategy of unresectable locally advanced non-small cell lung cancer - Zhang, Xiaofei; Zhang, Jianguo; Liu, Peiyi; Wang, Juan; Zhao, Kuaile; Zhu, Zhengfei; Gu, Kangsheng; Zhao, Weixin (Frontiers in Oncology, 2023)
Non-small cell lung cancer without sensitive mutations entered the splendid era of immunotherapy. This review aims to provide an evidence-based summary for immunotherapy for unresectable locally advanced non-small cell lung cancer, and references for clinical strategies of immunotherapy. Through literature review, the standard treatment for unresectable locally advanced non-small cell lung cancer should be radical concurrent radiotherapy and chemotherapy followed by consolidation immunotherapy. However, the efficacy of concurrent radiotherapy，chemotherapy combined with immunotherapy has not been improved, and its safety should be further validated. It is believed that induction immunotherapy plus concurrent radiotherapy and chemotherapy plus consolidation immunotherapy is promising. In clinical practice, the delineation of radiotherapy target should be relatively small. Pemetrexed combined with PD-1 inhibitor induces the strongest immunogenicity in chemotherapy. PD-L1 inhibitor is better in the combination treatment of radiotherapy, which presents significantly less adverse events.